2017
DOI: 10.1093/annonc/mdx230
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection versus watchful waiting in low-grade gliomas

Abstract: BackgroundInfiltrating low-grade gliomas (LGG; WHO grade 2) typically present with seizures in young adults. LGGs grow continuously and usually transform to higher grade of malignancy, eventually causing progressive disability and premature death. The effect of up-front surgery has been controversial and the impact of molecular biology on the effect of surgery is unknown. We now present long-term results of upfront surgical resection compared with watchful waiting in light of recently established molecular mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
156
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(161 citation statements)
references
References 34 publications
3
156
1
1
Order By: Relevance
“…37 Interestingly, we did not see a clear divergence of survival curves between young high-risk patients (below 40 years) and highrisk patients aged 40-49 years in our study. 3 Hence, a cutoff at 50 years seems more reasonable to select high-risk patients for early postoperative treatment, 1,40 to accurately balance the long-term risks against the benefits of treatment and to avoid overtreatment in long-term survivors. This is consistent with the findings from the UCSF group that used 50 years as a threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Interestingly, we did not see a clear divergence of survival curves between young high-risk patients (below 40 years) and highrisk patients aged 40-49 years in our study. 3 Hence, a cutoff at 50 years seems more reasonable to select high-risk patients for early postoperative treatment, 1,40 to accurately balance the long-term risks against the benefits of treatment and to avoid overtreatment in long-term survivors. This is consistent with the findings from the UCSF group that used 50 years as a threshold.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings from the UCSF group that used 50 years as a threshold. 3 Hence, a cutoff at 50 years seems more reasonable to select high-risk patients for early postoperative treatment, 1,40 to accurately balance the long-term risks against the benefits of treatment and to avoid overtreatment in long-term survivors.…”
Section: Discussionmentioning
confidence: 99%
“…An early follow-up found an overall survival benefit for patients treated with early surgical resection compared with those managed with biopsy and watchful waiting [16]. versus region A (14.4 years vs. 5.8 years, p < .01) [17]. These studies did not evaluate disease-specific survival, but they found that overall survival was similar to diseasespecific survival among patients with primary brain tumors (approximate 2% difference) in the Norwegian population [18].…”
Section: Gliomasmentioning
confidence: 98%
“…In the lack of randomization, propensity matching can, for example be, done to limit selection bias [16]. Also, differences in favored treatments between centers may enable pseudorandomized trials [11]. Collection of prospective data, for example within treatment registries may enable parallel cohort studies or pragmatic trials with sufficient statistical power.…”
mentioning
confidence: 99%